PERAN PROFESIONALISME GURU SKI MELALUI METODE STORYTELLING DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI MADRASAH IBTIDAIYAH - Fina Fadilatur Ramadhaniyah; Munawir Munawir; Titin Astriana (STKIP Subang, 2026)
This study aims to examine the role of professional teachers in teaching Islamic Cultural History (SKI) through the application of storytelling methods to improve the quality of learning in elementary madrasahs. The background of this study is based on low student participation caused by conventional teaching methods that are less innovative and teacher-centered. The approach used is a qualitative approach through a literature review, which includes the analysis of various scientific sources such as journals, books, and relevant previous studies. The results of the analysis indicate that the storytelling method, supported by teacher professionalism, is capable of enhancing learning motivation, conceptual understanding, and student engagement in the learning process. Professional teachers can design and implement creative, interactive, and enjoyable teaching strategies, ensuring that SKI material is presented in a contextual and easily understandable manner. Additionally, the storytelling method plays a role in instilling character values through meaningful narratives. Thus, the integration of teacher professionalism and the storytelling method makes a significant contribution to improving the quality of SKI learning in elementary madrasahs.